Hubungan sedentary lifestyle dengan fungsi kognitif lansia di UPT Pelayanan Sosial Tresna Werdha Jember - Ega Putri Nurwita; Tantut Susanto; Hanny Rasni (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2019)
Cognitive function disorders in elderly is one of the problems found in Indonesia. Cognitivefunction is related to a person’s lifestyle such as physical activity. Physical activity can increase brain nerve growth and affect cognitive function in elderly. However, the majority of the elderly choose sedentary lifestyle. Sedentary is a lifestyle by applying behavior when sitting, leaning back, and lying down which is done starting from waking up to the night before going to sleep continuously. The purpose of this study was to analyze the relationship between sedentary lifestyle and cognitive function among the elderly at UPT PSTW Jember. A cross-sectional design was conducted among 84 elderly at UPT PSTW Jember by using convenience sampling. A questionnaire was used to identify the sociodemography of participants while the data of sedentary lifestyle was obtained by using Global Physical Activity Questionnaire (GPAQ), and the data of cognitive function was taken using Mini Mental State Exam (MMSE). Spearman rank test was performed to answer the purpose of this study. Among 84 participants, it is shown that elderly are sedentary for 405 minutes/day, which are less than standard score (Ƶ = 1.377; p = 0.045). The cognitive function score of elderly is 27 which are greater than the standard score (Ƶ = 1.401; p = 0.040), so that the elderly has normal cognitive function. According to the result of the study, the sedentary lifestyle is related to cognitive function, the shorter duration of sedentary lifestyle, the cognitive function increases (r = -0.470; p < 0.001). Therefore, planned intervention is to make schedule routine physical activity and aerobic exercise to maintain cognitive function in elderly.